2015
DOI: 10.1093/icvts/ivv276
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and consequences of anastomotic leakage after Ivor Lewis oesophagectomy

Abstract: Anastomotic leakage after oesophagectomy is a major cause of postoperative morbidity and mortality. Identifying risk factors preoperatively can contribute to the prevention of postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 14 publications
3
59
0
Order By: Relevance
“…Our retrospective single‐center study revealed that the incidence of AL was 7.9%, which compared favorably with the rates reported by other studies . Previous studies have revealed many predictors of AL including heart failure, smoking, hypertension, renal insufficiency, preoperative albumin, and type of procedure . Our multivariate logistic regression analysis also indicated that surgical procedure and surgeon were independent risk factors of AL after esophageal cancer surgery.…”
Section: Discussionsupporting
confidence: 86%
“…Our retrospective single‐center study revealed that the incidence of AL was 7.9%, which compared favorably with the rates reported by other studies . Previous studies have revealed many predictors of AL including heart failure, smoking, hypertension, renal insufficiency, preoperative albumin, and type of procedure . Our multivariate logistic regression analysis also indicated that surgical procedure and surgeon were independent risk factors of AL after esophageal cancer surgery.…”
Section: Discussionsupporting
confidence: 86%
“…In previous reports, patients with the renal insufficiency, heart disease, diabetes, hypertension, previous stroke and chronic obstructive pulmonary disease were found to be at greater risk of developing AL [15][16][17] . Zehetner et al [18] suggested that disease processes that compromise anastomotic perfusion are major predictors of AL.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies on the risk factors for AL after esophagectomy have involved the mediastinal route and Ivor Lewis esophagogastrectomy [15][16][17][18][19][20][21] . In our study, the subcutaneous route was found to be an independent risk factor for AL in a multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It negatively affects postoperative morbidity and mortality [2], as well as recurrence-free and overall survival [3-5]. Currently, several studies have investigated patient-specific risk factors for the development of AL and described the management of postoperative AL [6, 7]. However, only few data are published on the typical time point of occurrence of postoperative AL, the favorable tool to diagnose postoperative AL (e.g., laboratory parameter analysis, endoscopy, cross-sectional imaging studies etc.)…”
Section: Introductionmentioning
confidence: 99%